Konsep Keimanan Ahlul Kitab(Studi Pemikiran Hamim Ilyas Dalam Dan Ahli Kitab Pun Masuk Surga) - Adriyansyah, Adriyansyah; , Dr. M. Muinidinillah Basri, M.A; , Dr. Syamsul Hidayat, M.Ag (2015)
Many people understand the teachings the teachings of Islam that comes from al-Qur'an and as-Sunnah, in a modern way, but the truth was actually leaving the absolute truth and khot'I , and become truths and relative. Studies which they claim a rational and scientific, but many found results that paradox with different proposition . Intellect would take precedence over the arguments of naqli in cases that are considered less rational with that background, this study aims to determine their concept so that no irregularities in its application. From this research can be obtained benefit both socially and academically, so as to contribute ideas on matters relating to confidence issues and amaliah especially in the concept of faith. This study includes qualitative research, the research to understand the phenomenon that is experienced by research subject and descriptive. Sources of data taken from various literature, references. The analysis was performed by combining the data from the data such data work, then carried tom her interpretation to grasp the meaning and relationships and draw conclusions from data that is obtained. From the research and analysis of the data and the conclusions people of the book is a Liberal perspective shallowness of thinking and their weaknesses in problem that just put faith above reason proposition naqli and qoth'i. What happened to the Liberal in understanding the concept of faith with the wrong understanding departing from here make the importance of this study